2022
DOI: 10.1186/s12909-022-03170-8
|View full text |Cite
|
Sign up to set email alerts
|

Nursing faculty experiences with student incivility in South Korea: a qualitative study

Abstract: Background Student academic incivility is a serious problem in nursing education because it negatively influences the learning process, wellbeing of faculty members, and faculty–student relationships. The aim of this study was to explore nursing faculty experiences related to student incivility in nursing education. Methods We used an exploratory qualitative methodology and conducted in-depth interviews with 14 nursing faculty members working at 11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…13,14 The enactment of learning policies resulted in a lack of interaction between lecturers and students which led to feelings of loss. Which has an impact on the student's lack of politeness, other research found nursing students indifferent to teacher expectations 15 , on the other hand 16 mentions that distance education is not suitable for nursing education and basic practical skills of nursing, the distance education system does not operate well enough, and is not suitable for conducting mandatory clinical practice for nursing. While in this study some students find ways to engage with each other, courses can offer active online learning strategies that allow students to collaborate through group work, sharing video messages, and soliciting student feedback regularly.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 The enactment of learning policies resulted in a lack of interaction between lecturers and students which led to feelings of loss. Which has an impact on the student's lack of politeness, other research found nursing students indifferent to teacher expectations 15 , on the other hand 16 mentions that distance education is not suitable for nursing education and basic practical skills of nursing, the distance education system does not operate well enough, and is not suitable for conducting mandatory clinical practice for nursing. While in this study some students find ways to engage with each other, courses can offer active online learning strategies that allow students to collaborate through group work, sharing video messages, and soliciting student feedback regularly.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, many quantitative and qualitative studies on the experiences of clinical incivility among nursing students in South Korea have been conducted [15,43,56,58,63,64]. However, little research exists regarding clinical incivility management interventions for pre-licensure nursing students in South Korea.…”
Section: Discussionmentioning
confidence: 99%
“…Then a semi-structured, one-to-one, in-depth interview was carried out among the participants. The interview outline was formulated concerning relevant literature [ 15 , 17 ] and the results of the initial part of this study about workplace violence among nursing students. It mainly found that nursing students’ experiences of violence are mainly related to factors such as personality, gender, internship time, and other factors.…”
Section: Methodsmentioning
confidence: 99%
“…These reactions can lead to a poor sense of professional identity [ 7 9 ]. Currently, there are several qualitative studies on nursing students’ experiences of violence in clinical settings, but most mainly focus on females, and less focused on males [ 5 , 7 , 11 , 15 – 17 ]. The theory of gender differences points out that men and women have different specific behaviors, basic attitudes, and feelings in the same environment [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%